Fiqh and Astronomical Rashdul Qibla; Determining the Direction of the Qibla by Using a Stellarium - Sayehu Sayehu; Aspandi Aspandi (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2023)
The existence of celestial bodies has many functions, such as worship interests as a guide to prayer time. When praying, it is necessary to face the Qibla, the Kaaba. Finding the direction of the Qibla is facilitated by Rashdul Kibla, which is based on observations of celestial bodies, including the Sun and constellations. The Stellarium application is one of the technological developments that can be used as a medium in determining the Qibla direction. This study aims to describe the concept of fiqh and astronomy rashdul qibla and the use of stellarium application as a medium for determining the qibla direction. Through a qualitative approach with descriptive-analytical method, this research describes the fiqh of rashdul qibla, astronomy of rashdul qibla and how to use the stellarium application as a medium for determining the qibla direction. The data source of this research is obtained through documentation of written works of fiqh and astronomy concepts that provide explanations related to rashdul qibla and the stellarium application. The results showed that the determination of the Qibla direction through rashdul qibla will be easier and measurable. The astronomical Qibla direction is part of the form of measuring, comparing and finding the Qibla direction whose accuracy is not in doubt. Stellarium is part of an IT-based application that can be used as a means of determining the Qibla direction whose calculation accuracy can be adjusted to the place where the Qibla direction is sought.